Publisher Correction: Letter perception emerges from unsupervised deep learning and recycling of natural image features. (November 2017) - Testolin, Alberto; Stoianov, Ivilin; Zorzi, Marco
In the version of this Letter originally published, in the sentence beginning "Written symbols are culture specific...", in the second example, 'Φ' was used instead of 'F'; it should have read '(for example, ℱ versus F)'. This has now been corrected in all versions of the Letter.